Aktivitas enzim monooksigenase pada populasi nyamuk Aedes aegypti di Kecamatan Tembalang, Kota Semarang - Dyah Widiastuti; Sunaryo Sunaryo; Nova Pramestuti; Martini Martini (ASPIRATOR - Journal of Vector-borne Disease Studies, 2015)
Dengue Haemorrhagic Fever (DHF) is a major health problem in Tembalang sub district, Semarang City. Fogging with insecticide applications was done frequently as an effort to control Dengue vectors. The use of insecticides from the same class in a long time can lead to resistance in mosquitos’ population. The research aimed to observe the activity of monooxygenases in Aedes aegypti populations in Tembalang Subdistrict, Semarang. The study was conducted during February-November 2014 with a cross-sectional design in 10 villages in Tembalang Subdistirict, Semarang City. Field strains of Ae. aegypti eggs were collected using ovitraps. The collected eggs were grown under standard condition to adult mosquitoes. Mosquitos’ homogenate were stored at -85°C and used for biochemical assays. The results showed there was increased monooxygenases activity in Ae. aegypti populations. Resistance to synthetic pyrethroid insecticide in Ae. aegypti mosquitoes population in Tembalang Subdistrict might be caused by the mechanism of detoxification enzymes in particular monooxygenases